Humoral Reactivity of Renal Transplant-Waitlisted Patients to Cells From GGTA1/CMAH/B4GalNT2, and SLA Class I Knockout Pigs. Issue 4 (April 2017) - Martens, Gregory R.; Reyes, Luz M.; Butler, James R.; Ladowski, Joseph M.; Estrada, Jose L.; Sidner, Richard A.; Eckhoff, Devin E.; Tector, Matt; Tector, A. Joseph
Abstract : Background: Antipig antibodies are a barrier to clinical xenotransplantation. We evaluated antibody binding of waitlisted renal transplant patients to 3 glycan knockout (KO) pig cells and class I swine leukocyte antigens (SLA). Methods: Peripheral blood mononuclear cells from SLA identical wild type (WT), α1, 3-galactosyltransferase (GGTA1) KO, GGTA1/ cytidine monophosphate-N-acetylneuraminic acid hydroxylase (CMAH) KO, and GGTA1/ CMAH /b1, 4 N-acetylgalactosaminyl transferase (B4GalNT2) KO pigs were screened for human antibody binding using flow cytometric crossmatch (FCXM). Sera from 820 patients were screened on GGTA1/CMAH/B4GalNT2 KO cells and a subset with elevated binding was evaluated further. FCXM was performed on SLA intact cells and GGTA1/SLA class I KO cells after depletion with WT pig RBCs to remove cell surface reactive antibodies, but leave SLA antibodies. Lastly, human and pig reactive antibodies were eluted and tested for cross-species binding and reactivity to single-antigen HLA beads. Results: Sequential glycan KO modifications significantly reduce antibody binding of waitlisted patients. Sera exhibiting elevated binding without reduction after depletion with WT RBCs demonstrate reduced binding to SLA class I KO cells. Human IgG, eluted from human and pig peripheral blood mononuclear cells, interacted across species and bound single-antigen HLA beads in common epitope-restricted patterns. Conclusions: Many waitlisted patients have minimal xenoreactive antibody binding to the triple KO pig, but some HLA antibodies in sensitized patients cross-react with class I SLA. SLA class I is a target for genome editing in xenotransplantation. Abstract : Martens et al report that most waitlisted patients have minimal antibody binding to triple glycan KO cells, but HLA antibodies from some sensitized patients can cross-react with class I SLA, thus suggesting another antigen target for genome editing in xenotransplantation. Supplemental digital content is available in the text.